Pest management practices of farmers and impact of pesticides on maize, water and community in Adamawa, Nigeria - Ahmed, Mohammed (2018)
Maize is an essential cereal crops that is widely cultivated in Adamawa state, Nigeria. It is cultivated and consumed as a staple food. Pesticide is one the most common pest management method used by maize farmers to reduce the impacts from pest which contributed to yield declined. Many researches had been conducted on impact of pesticide residues on different types of vegetables and tree crops but little or no study have been conducted on impact of pesticide residues on maize and water and its risks on human. In order to bridge these gaps, the objective of this study focused on pest management practices of maize, the residue of pesticides used in maize and water, and its risk on the community in Adamawa state, Nigeria. Structured questionnaire was constured and distributed to respondents. Random sampling technique was employed to select the respondents in the four study areas which are Chigari, Dasin Hausa, Gurin and Lake Gerio, with 80 farmers in each areas, hence the total number of respondents for the study was 320. During the survey, questions on the total amount of maize and water consumed and mean weight of farmers were included. The data from survey were analysed with pearson correllation, descriptive and factor analysis using SPSS software. The pesticide and the residues of commonly used by farmer in the study areas were extracted and analysed from maize and water using QuEChERS and DLLME method respectively. The risk on community were counted following the determination of Estimated Daily Intake (EDI) of water and maize from the area. The pest management survey’s result shows pesticide is the main pest management practices by the farmers. Three types of pesticide commonly used are organochlorine, organophosphate and pyrethroids. There were 19 residues of organochlorines, organophosphates and pyrethroids were found higher in water than the maize samples from the study areas. The residue analysis in maize and water indicated that organochlorine pesticide residues in water were mostly above European Maximum Residue Level (EU MRL) with few of organophosphates and pyrethroid, but lower in maize samples across the study areas. The findings from pesticide residue risk assessment shown that water samples contained the most contaminants from all the areas which are cypermethrin, permethrin, bifenthrin, malathion and diazinon. In regard to areasthe results indicated that Lake-Gerio has the highest risk cases of prevalent pesticide residues contaminants and Dasin-Hausa has the lowest risk cases among the four areas under study. Most farmers in the study areas lack adequate knowledge of correct principles of pest management practices due to poor educational background that led to neglecting necessary precautionary measures. This might be due to lack of extension services to rural farmers on part of the government. There is need to create awareness among farmers on Integrated Pest Management (IPM) system and Good Agricultural Practices (GAP) that is environmentally friendly.